Effect of high-intensity-intervall training on cardiovascular function, VO2max, and muscular force - Astorino, T. A.; Allen, R. P.; Roberson, D. W.; Jurancich, M. (The Journal of Strength and Conditioning Research, 2012)
The purpose of this study was to examine the effects of short-term high-intensity interval training (HIIT) on cardiovascular function, cardiorespiratory fitness, and muscular force. Active, young (age and body fat = 25.3 ± 4.5 years and 14.3 ± 6.4%) men and women (N = 20) of a similar age, physical activity, and maximal oxygen uptake (VO2max) completed 6 sessions of HIIT consisting of repeated Wingate tests over a 2- to 3-week period. Subjects completed 4 Wingate tests on days 1 and 2, 5 on days 3 and 4, and 6 on days 5 and 6. A control group of 9 men and women (age and body fat = 22.8 ± 2.8 years and 15.2 ± 6.9%) completed all testing but did not perform HIIT. Changes in resting blood pressure (BP) and heart rate (HR), Vo2max, body composition, oxygen (O2) pulse, peak, mean, and minimum power output, fatigue index, and voluntary force production of the knee flexors and extensors were examined pretraining and posttraining. Results showed significant (p < 0.05) improvements in Vo2max, O2 pulse, and Wingate-derived power output with HIIT. The magnitude of improvement in Vo2max was related to baseline VO2max (r = -0.44, p = 0.05) and fatigue index (r = 0.50, p < 0.05). No change (p > 0.05) in resting BP, HR, or force production was revealed. Data show that HIIT significantly enhanced VO2max and O2 pulse and power output in active men and women.